Mechanistic Insights into Trop2 Clustering on Lung Cancer Cell Membranes Revealed by Super-resolution Imaging - Fu, Yilin (ACS Omega, 2020)
[Image: see text] The transmembrane glycoprotein Trop2 plays important roles in various types of human cancers, especially lung cancer. Although it has been found to form clusters on cancer cell membranes, the factors that affect its clustering are not yet fully understood. Here, using direct stochastic optical reconstruction microscopy (dSTORM), we found that Trop2 generated more, larger, and denser clusters on apical cell membranes than on basal membranes and that the differences might be related to the different membrane structures. Moreover, dual-color dSTORM imaging revealed significant colocalization of Trop2 and lipid rafts, and methyl-β-cyclodextrin disruption dramatically impaired the formation of Trop2 clusters, indicating a key role of lipid rafts in Trop2 clustering. Additionally, depolymerization of the actin cytoskeleton decreased Trop2 cluster numbers and areas, revealing that actin can stabilize the clusters. More importantly, stimulation of Trop2 in cancer cells hardly changed the cluster morphology, suggesting that Trop2 is activated and forms clusters in cancer cells. Altogether, our work links the spatial organization of Trop2 to different membrane structures and Trop activation and uncovers the essential roles of lipid rafts and actin in Trop2 cluster maintenance.